SARA Hoax: Phenomena, Meaning, and Conflict Management - Nikolaus Ageng Prathama; MJ Rizqon Hasani; Muhammad Irali Akbar (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2022)
The SARA (Ethnic, Religion, Race, and Intergroup) hoax is one of the disquieting hoaxes as it has the potential to cause conflict. Some Indonesians might not know that the SARA information they get is factual or hoaxes, which can lead to prejudice. Conflict in Tanjung Balai and Depok shows that exposure to SARA hoaxes can affect individual behavior. This study aims to describe individual experiences in interacting with SARA information and performing conflict management. This study uses phenomenological methods and in-depth interview instruments, allowing researchers to interact with the world of the informants’ conscious experiences. The results indicate that the informants access various information related to the main activities. The internet has become the preferred media gratification. From the information-seeking activities, some SARA information was found, and some SARA information were hoaxes. SARA hoax has three meanings and has the potential to cause conflict. Hence, informants applied different conflict management styles in dealing with conflicts that arose.